Influence of early intervention programmes on the language development of pupils with hearing impairment in Ilorin, Kwara State, Nigeria (2014)
Hearing impairment is a condition that mostly leads to poor language development, and thereby affects the academic performance of people with the disorder. Due to this developmental lags, this study investigated the influence of early intervention programmes on the language development of children with hearing impairment in Ilorin, Kwara State. A correlational research design was adopted for the study. 100 purposively- selected pupils with hearing impairment from three special primary schools formed the participants for the study, and were distributed into three groups of early identified, early identified and enrolled, and the later identified. Three instruments- Peabody Picture Vocabulary Test (PPVT)(r=0.85), to test for vocabulary skill, Pre-Language Scale Instrument (r=0.78), to test for verbal reasoning skills, and Family Involvement Rating Scale (r= 0.89), to test for the participation of parents of pupils with hearing impairment in parenting were used to answer the three research questions and test the three research hypotheses at 0.05 level of significance generated for the study. The data collected were analyzed using Pearson’s Product Moment Correlation Coefficient, Percentage, Frequency counts and Multiple Regression Analysis. A significant relationship was found among the early intervention programmes (age of identification, age of enrolment and parental involvement) on the language development of pupils with hearing impairment (F(84.439)=218,P>0.05), and each of the early intervention programmes (age of identification (F(527)=195.P>0.05), age of enrolment (F(833)=195,p>0.05) and parental involvement (F(.210)=.195,P>0.05) had significant relationship with the language development of pupils with hearing impairment. Therefore, administrators should make the provision of hearing screening result a prerequisite for admitting pupils into the school for better placement.